EVALUASI PELAKSANAAN PROGRAM GERAKAN LITERASI SEKOLAH TAHUN 2023/2024 DI SD NEGERI DUKUH 05 SALATIGA MENGGUNAKAN CIPP - Astri, Ratna Putri; Krisma Widi Wardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is an evaluative study using a qualitative approach. In this study the evaluation model used is Context, Input, Process, and Product (CIPP) developed by Stufflebum. The objective of this research is to find out: 1) Context of implementation of the School Literacy Movement program, 2) Inputs of the implementation program of School Literation Movement in, 3) Process of implementing the school literacy movement program, and 4) Products of execution of the school Literation movement program in SD State Dukuh 05. Data collection on research is by observation techniques, interviews, and documentation. The results of this research are based on the context of the implementation of the school literacy movement program in the good category, then the Input implementation aspect of the School Literacy Movement program is in the fairly good category. Then for the aspect of School Literation Movement Program Implementation Process is in a good category and the Product implementation aspects of the Education Movement programme are in the right category. The results show that the evaluation of school literation movement program implementation in SD State Dukuh 05 is performing well, this is seen from the performance of the program activities based on levels of cultivation, development, and learning stages have been carried out in the SD State dukuh 05 in accordance with the guidelines for implementing School Literature Movement.